2013
DOI: 10.3329/jdnmch.v18i2.16012
|View full text |Cite
|
Sign up to set email alerts
|

Short term catheterization versus long term catheterization after vaginal prolapsed surgery: A randomized control trial in Dhaka National Medical College & Hospital

Abstract: Objective: This study was undertaken to determine whether short term bladder catheterization would be more beneficial than the routinely practiced long term catheterization after vaginal hysterectomy for prolapsed uterus.  Materials and methods: This randomized controlled trial was conducted in Obstetrics and Gynecology Department of Dhaka National Medical College Hospital from January 2009 to January 2011. A total of 106 women were included in this study. They were randomized into short term catheterization g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Prolong catheterization after vaginal prolapse surgery is believed to be preventing voiding problem post operatively. 18 But mean time of first voiding after removal of catheter was almost equal in both groups in this study. Majority of women had 1-2 hrs first voiding time after removal of catheter in both groups and duration of catheter did not affect the first voiding time in both groups when first voiding time was divided into < 2 hours and > 2 hours).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Prolong catheterization after vaginal prolapse surgery is believed to be preventing voiding problem post operatively. 18 But mean time of first voiding after removal of catheter was almost equal in both groups in this study. Majority of women had 1-2 hrs first voiding time after removal of catheter in both groups and duration of catheter did not affect the first voiding time in both groups when first voiding time was divided into < 2 hours and > 2 hours).…”
Section: Discussionmentioning
confidence: 47%
“…19 The Residual Urinary Volume (RUV) after removal of catheter can be taken as functional bladder parameter and the value <200 ml placed as normal. 18 In this study 6% of the women in group A and 2% in group B had residual volume of urine >200 ml but residual volume of urine after removal of catheter is significantly high in long term catheterization group when residual urine volume was divided into <100ml and >100ml). Another study showed that none of the women had residual volume of urine >200ml in both group and mean residual volume in significantly high in long term group than short term catheterization group (10152.38 ml and 59.1937.87 ml) 18 .…”
Section: Discussionmentioning
confidence: 53%